Analysis of Additional Methods of purification of Mixtures while Conducting Differential Lysis under Sexual Crimes - Ya. O. Sinitsyna (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on the problem of studying mixed biological traces during the research of the growing number and severity of sexual crimes. The presence of blood and epithelial cells with a small amount of sperm on things removed at the crime scene and smears from the victim’s body, complicates the molecular and genetic examination and the likelihood of obtaining a quality DNA profile from the sperm of the rapist. Therefore, the author has defined chemical basis of the standard method of differential lysis and the correlation of the components of the mixture of epithelial cells and sperm, which can help to get mixed and pure DNA profiles while amplify using the sets AmpFlSTR® Identifiler® PCR Amplification Kit, GlobalFiler STR PCR Amp Afication ™ PCR Amplification Kit. The author has analyzed literature data on the developed and perspective methods and additional stages of the differential lysis technique for purification of the mixture and aimed at sorting and reducing the number of epithelial cells. Chemical methods of mixture purification have been studied, including additional washing and incubation of the mortar, use of DNases, SDS lysis buffer and magnetic sorting with the use of antibodies (MOSPD3 and RH-20), and physical methods such as laser microdissection, acoustic lysis, hydrodynamic effect in small Reynolds numbers, microchips with additional integration of Cialyl Lewis oligosaccharide sequence and DEPArray technology. The main advantages and disadvantages of the procedures, the possibility of combining with other types, the impact on subsequent stages of molecular and genetic examination and the possibility of automating the research process have been provided for the methods. For the methods, the author has studied the probability of contamination during the procedure and the possibility of using for obsolete traces of sperm, where the destruction of sperm structure occurred. The author has indicated the possibility of automation of physical systems for forensic examination of molecular and genetic analysis by integrating the stages of sample preparation, cell counting and DNA isolation on a single device, which will reduce the time of the analysis of research objects in the future. The analysis of the literature data showed an improvement in the quality of DNA profiles while using the above methods, so it has been offered to use the presented methods for testing in expert practice.